Elotuzumab in combination with lenalidomide and dexamethasone in patients with relapsed multiple myeloma: final phase 2 results from the randomised, open-label, phase 1b–2 dose-escalation study. Issue 12 (December 2015) - Richardson, Paul G; Jagannath, Sundar; Moreau, Philippe; Jakubowiak, Andrzej J; Raab, Marc S; Facon, Thierry; Vij, Ravi; White, Darrell; Reece, Donna E; Benboubker, Lotfi; Zonder, Jeffrey; Tsao, L Claire; et al.
Summary: Background: Elotuzumab, an immunostimulatory monoclonal antibody targeting signalling lymphocytic activation molecule (SLAM) family member 7 (SLAMF7), selectively kills SLAMF7-expressing myeloma cells through direct activation and engagement of the innate immune system, and thus might have clinical benefit in the treatment of myeloma. In phase 1 of this phase 1b–2 study, 82% of patients with relapsed multiple myeloma who were given elotuzumab plus lenalidomide and dexamethasone achieved an overall response. Here we report the final phase 2 results. Methods: We did this randomised, multicentre, open-label, dose-escalation study (1703) at 17 hospitals in the USA, Canada, France, and Germany. Patients aged at least 18 years with confirmed, relapsed multiple myeloma, Eastern Cooperative Oncology Group performance status 0–2, and one to three previous therapies but no previous lenalidomide were eligible for phase 2. We randomly assigned patients (1:1) to either 10 mg/kg or 20 mg/kg intravenous elotuzumab plus oral lenalidomide (25 mg) and dexamethasone (40 mg). We stratified patients on the basis of the number of previous therapies (one versus two or three), and status of previous treatment with immunomodulatory drugs (yes or no), and used permuted block randomisation with a block size of four. Treatment was given in 28-day cycles until disease progression or unacceptable toxic effects occurred (elotuzumab was given on days 1, 8, 15, and 22 for cycles 1 to 2 and days 1 and 15 for subsequent cycles; lenalidomide was given on days 1–21 and dexamethasone once per week). The primary endpoint was the proportion of patients who achieved an objective response according to International Myeloma Working Group criteria. Primary analyses were done in the intention-to-treat population, and safety was analysed in all patients who received at least one dose of study drugs. This study is registered withClinicalTrials.gov, numberNCT00742560 . Findings: Between Jan 4, 2010, and Dec 21, 2010, we recruited and randomly assigned 73 patients to elotuzumab (36 to 10 mg/kg, 37 to 20 mg/kg). At data cutoff (Jan 16, 2014), 13 patients remained on treatment (six on 10 mg/kg, seven on 20 mg/kg). 61 (84%) patients achieved an objective response (33 [92%] with 10 mg/kg, 28 [76%] with 20 mg/kg); 31 (42%) a very good partial response (17 [47%] with 10 mg/kg, 14 [38%] with 20 mg/kg); and 20 (27%) a partial response (10 [28%] with 10 mg/kg, 10 [27%] with 20 mg/kg). The most common treatment-emergent adverse events of any grade were diarrhoea (48 [66%]), muscle spasms (45 [62%]), and fatigue (41 [56%]). 57 (78%) patients had grade 3–4 events, the most common of which were lymphopenia (15 [21%]) and neutropenia (14 [19%]). Three deaths occurred, none related to the study drugs. Interpretation: Elotuzumab combined with lenalidomide and dexamethasone in patients with relapsed multiple myeloma showed acceptable safety and efficacy that seems better than that previously noted with lenalidomide and dexamethasone only. Phase 3 trials are in progress. Funding: Bristol-Myers Squibb, AbbVie Biotherapeutics.